Correction: Characterization of a carboxyl methyltransferase in Fusarium graminearum provides insights into the biosynthesis of fusarin A. Issue 30 (23rd July 2021) - Yang, Qian; Wang, Wanqiu; Lin, Yueting; Lin, Yuqi; Tang, Zhijun; Wang, Jing; Tao, Jiang; Tang, Weihua; Liu, Wen
Abstract : Correction for 'Characterization of a carboxyl methyltransferase in Fusarium graminearum provides insights into the biosynthesis of fusarin A' by Qian Yang et al., Org. Biomol. Chem., 2021, DOI: ; 10.1039/d1ob01010g .